Protein Prenylation in Plant Stress Responses - Hála, Michal; Žárský, Viktor (Molecules, 2019)
Protein prenylation is one of the most important posttranslational modifications of proteins. Prenylated proteins play important roles in different developmental processes as well as stress responses in plants as the addition of hydrophobic prenyl chains (mostly farnesyl or geranyl) allow otherwise hydrophilic proteins to operate as peripheral lipid membrane proteins. This review focuses on selected aspects connecting protein prenylation with plant responses to both abiotic and biotic stresses. It summarizes how changes in protein prenylation impact plant growth, deals with several families of proteins involved in stress response and highlights prominent regulatory importance of prenylated small GTPases and chaperons. Potential possibilities of these proteins to be applicable for biotechnologies are discussed.
Keywords: rostlinné proteiny; Protein Prenylation; biotechnologie; Stress, Physiological; rostliny; fyziologický stres; Substrate Specificity; substrátová specifita; Biotechnology; prenylace proteinů; Plants; Plant Proteins